Structure-Based Design of Head-Only Fusion Glycoprotein Immunogens for Respiratory Syncytial Virus. - Jeffrey C Boyington; M Gordon Joyce; Mallika Sastry; Guillaume B E Stewart-Jones; Man Chen; Wing-Pui Kong; Joan O Ngwuta; Paul V Thomas; Yaroslav Tsybovsky; Yongping Yang; Baoshan Zhang; Lei Chen; et al. (PLoS ONE)
Respiratory syncytial virus (RSV) is a significant cause of severe respiratory illness worldwide, particularly in infants, young children, and the elderly. Although no licensed vaccine is currently available, an engineered version of the metastable RSV fusion (F) surface glycoprotein-stabilized in the pre-fusion (pre-F) conformation by "DS-Cav1" mutations-elicits high titer RSV-neutralizing responses. Moreover, pre-F-specific antibodies, often against the neutralization-sensitive antigenic site Ø in the membrane-distal head region of trimeric F glycoprotein, comprise a substantial portion of the human response to natural RSV infection. To focus the vaccine-elicited response to antigenic site Ø, we designed a series of RSV F immunogens that comprised the membrane-distal head of the F glycoprotein in its pre-F conformation. These "head-only" immunogens formed monomers, dimers, and trimers. Antigenic analysis revealed that a majority of the 70 engineered head-only immunogens displayed reactivity to site Ø-targeting antibodies, which was similar to that of the parent RSV F DS-Cav1 trimers, often with increased thermostability. We evaluated four of these head-only immunogens in detail, probing their recognition by antibodies, their physical stability, structure, and immunogenicity. When tested in naïve mice, a head-only trimer, half the size of the parent RSV F trimer, induced RSV titers, which were statistically comparable to those induced by DS-Cav1. When used to boost DS-Cav1-primed mice, two head-only RSV F immunogens, a dimer and a trimer, boosted RSV-neutralizing titers to levels that were comparable to those boosted by DS-Cav1, although with higher site Ø-directed responses. Our results provide proof-of-concept for the ability of the smaller head-only RSV F immunogens to focus the vaccine-elicited response to antigenic site Ø. Decent primary immunogenicity, enhanced physical stability, potential ease of manufacture, and potent immunogenicity upon boosting suggest these head-only RSV F immunogens, engineered to retain the pre-fusion conformation, may have advantages as candidate RSV vaccines.